Development of the European Healthcare and Social Cost Database (EU HCSCD) for use in economic evaluation of healthcare programs - Jaime Espín; Zuzana Špacírová; Joan Rovira; David Epstein; Antonio Olry de Labry Lima; Leticia García-Mochón (BMC, 2022)
Abstract Introduction Costs are one of the critical factors for the transferability of the results in health technology assessment and economic evaluation. The objective is to develop a cost database at the European level to facilitate cross-border cost comparisons in different settings and explains the factors that lead to differences in healthcare costs in different countries, taking into account the differences between health systems and other factors. Methodology The core of the database is compounded of three main categories (primary resources, composite goods and services, and complex processes and interventions) organized into 13 subcategories. A number of elements providing as detailed information of unit cost as possible were identified in order to mitigate the problem of comparability. Consortium partners validated both the database structure and selected costing items. Results Twenty-seven costing items included in the EU HCSCD resulted in 1450 unit costs when taking into account all item subtypes and countries. Cross-country differences in costs are driven by the type of resources included in the costing items (e.g., overhead costs in case of complex processes and interventions) or by the variety of existing brands and/or models and the type of unit value in most of the primary resources. Conclusion The EU HCSCD is the only public unit healthcare and social cost database at European level that gather data on unit costs and explains differences in costs across countries. Its maintenance and regular data updating will enable establishing specific systems for generating and recording information that will meet many of its current limitations.